Orphans in American Fiction - Vašíčková, Marcela (Univerzita Pardubice, 2010)
This paper focuses on the issue of orphans in the nineteenth and the twentieth century. The thesis analyzes the novels The Cider House Rules and The Adventures of Huckleberry Finn, where different concepts of orphanage are introduced. Presented in this analysis are also the topics relating to the status of the orphans, their childhood, their position in society and relationships, their characteristic features influenced by their lives and the question of loneliness and inferiority. The paper also briefly describes theoretical background of the views of childhood and orphans in the nineteenth and the twentieth century and compares both novels from the point of view of their attitude to the issues presented.
Sirotci v americkém románu
Keywords: americká literatura; Twain, Mark; Irving, John; dětství; Děti; sirotci; sirotčince; American literature; childhood; Children; orphans; orphanages